Continuous conversion of CO2 to alcohols in a TiO2 photoanode‐driven photoelectrochemical system. Issue 7 (23rd January 2020) - Castro, Sergio; Albo, Jonathan; Irabien, Angel
Abstract: BACKGROUND: The recycling of CO2 by photoelectrochemical reduction has attracted wide interest due to its potential benefits when compared to electro‐ and photo‐catalytic approaches. Among the various available semiconductors, TiO2 is the most employed material in photoelectrochemical cells. Besides, Cu is a well‐known electrocatalyst for the production of alcohols from CO2 reduction. RESULTS: A photoelectrochemical cell consisting of a TiO2 ‐based membrane electrode assembly (MEA) photoanode and a Cu plate is employed to reduce CO2 to methanol and ethanol continuously under UV illumination (100 mW cm −2 ). A maximum increment of 4.3 mA cm −2 in current between the illuminated and dark conditions is achieved at −2 V versus Ag/AgCl. The continuous photoelectrochemical reduction process in the filter‐press cell is evaluated in terms of reaction rate ( r ), as well as Faradaic efficiency ( FE ) and energy efficiency ( EE ). At −1.8 V versus Ag/AgCl, a maximum reaction rate of r = 9.5 μmol m −2 s −1, FE = 16.2% and EE = 5.2% for methanol and r = 6.8 μmol m −2 s −1, FE = 23.2% and EE = 6.8% for ethanol can be achieved. CONCLUSIONS: The potential benefits of the photoanode‐driven system, in terms of yields and efficiencies, are observed when employing a TiO2 ‐based MEA photoanode and Cu as dark cathode. The results demonstrate first the effect of UV illumination on current density, and then the formation of alcohols from the continuous photoreduction of CO2 . Increasing the external applied voltage leads to an enhanced production of methanol, but decreases ethanol formation. The system outperforms previous photoanode‐based systems for CO2 ‐to‐alcohols reactions. © 2019 Society of Chemical Industry